625 The Impact of the Mexico-San Diego Border Wall Extension on Spinal Injuries. (April 2023) - Tenorio, Alexander; Brandel, Michael G.; Produturi, Gautam; McCann, Carson; Costantini, Todd; Doucet, Jay; Ciacci, Joseph D.
Abstract : INTRODUCTION: San Diego, California has one of the busiest international land borders in the world, and its unauthorized crossing is a contentious issue. The recent border height extension along the San Diego-Mexico border has led to a new set of physical risks to unauthorized individuals traversing the wall. METHODS: In this retrospective cohort study, patients who presented to the UC San Diego Trauma Center between 2016 and 2021 were considered. Two different cohorts were compared: pre-height extension (Jan 2016-May 2018), and post-height extension (January 2020-December 2021). Demographics, clinical data (fracture morphology, operative intervention, concurrent injuries, length of stay), and hospital costs were collected. Spinal injuries were normalized using Customs and Border Protection (CBP) apprehensions to adjust for changing migration rates. Statistical analysis was completed with Stata MP Version 14.1 (Stata Corp LP). RESULTS: A total of 114 patients met inclusion criteria: 12 in the pre-height extension period, and 102 in the post-height extension period. The increase in spine injuries per month (0.8 to 4.25) and operative spine injuries per month (0.3 to 1.7) were statistically significant (P < 0.001). Concurrent extremity injuries were also significantly increased (8.3 vs. 43.1%, p = 0.02). The severity of injuries and economic costs were reflected in median length of stay (6 vs. 9 days; p = 0.006) and median total hospital charges ($150, 914 to $293, 798; p < 0.001). CONCLUSIONS: The data support that the San Diego-Mexico border wall extension is correlated with more frequent, severe, and costly spinal injuries. These findings advocate for reevaluating our current border wall infrastructure as this represents a humanitarian and public health crisis.